Comparison of self-reported energy availability and metabolic hormones to assess adequacy of dietary energy intake in young elite athletes - Koehler, K.; Achtzehn, S.; Braun, H.; Mester, J.; Schaenzer, W. (Applied Physiology, Nutrition, and Metabolism, 2013)
Previous intervention studies suggest that leptin, insulin, insulin-like growth factor 1 (IGF-1), and triiodthyronine (T3) are sensitive markers of inadequate energy intake in relation to exercise expenditures. Because of limitations in metabolic hormone measurements, self-reported energy availability (EA) based on food and activity records may present an alternative for characterizing energy status in young athletes. The purpose of the current study was to assess whether self-reported EA is related to leptin, insulin, IGF-1, and T3 in 352 young athletes. Sex, body composition, sport participation, and acute weight changes were considered as confounding variables. Multiple linear regression revealed that EA was negatively associated with leptin (p < 0.05) but not with insulin, IGF-1, or T3. Female athletes with low EA (<30 kcal·kg-1 fat-free mass (FFM)) had higher leptin concentrations (5.0 ± 4.7 ng/mL) and more body fat (18.3% ± 5.1%) than did females with normal EA (leptin, 3.1 ± 2.4 ng/mL; body fat, 15.8% ± 4.2%; both, p < 0.001). Athletes reporting acute weight loss (>1 kg·week-1) had a lower EA (18.9 ± 7.4 kcal/kg FFM) than did weight-stable athletes (30.0 ± 11.2 kcal/kg FFM) or athletes reporting weight gain (>1 kg; 49.7 ± 13.1 kcal/kg FFM). IGF-1 and T3 were also reduced in athletes who lost weight (p < 0.01). This cross-sectional study reveals a lack of association between self-reported EA and metabolic hormones indicative of energy status in young athletes. Further studies are needed to investigate whether self-reported EA and metabolic hormones are in better agreement when measured repeatedly.